Dampak Kebiasaan Tidur Larut Malam dan Hubungannya terhadap Kejadian Malaria - Ardiansa, Ardiansa; Ester, Ester (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study examines the impact of sleeping late at night and its relationship with the incidence of malaria. This research method uses observational analytics with a cross-sectional study approach. The study results showed that the habit of sleeping late at night on malaria incidence obtained a P value of 0.000. In conclusion, there is a relationship between the practice of sleeping late at night and the incidence of malaria at the Samabusa Community Health Center, Nabire Regency. Keywords: Late Night Sleeping Habits, Malaria, Samabusa